HIV-1 Immunogen: an overview of almost 30 years of clinical testing of a candidate therapeutic vaccine. (2nd July 2016) - Graziani, Gina M.; Angel, Jonathan B.
ABSTRACT: Introduction : Although current antiretroviral therapy (ART) has transformed HIV infection into a chronic, manageable disease, ART does not cure HIV infection. Furthermore, the majority of the world's infected individuals live in resource-limited countries in which access to ART is limited. Thus, the development of an effective therapeutic HIV vaccine would be an invaluable treatment alternative. Areas covered : Developed by the late Dr. Jonas Salk, HIV-1 Immunogen (Remune®) is a candidate therapeutic vaccine that has been studied in thousands of HIV-infected individuals in more than a dozen clinical trials during almost three decades. This Drug Evaluation, which summarizes the results of these trials that have shown the vaccine to be safe and immunogenic, also discusses the contradictory and controversial conclusions drawn from the phases 2, 2/3 and 3 trials that assessed the clinical efficacy of this vaccine. Expert opinion : Given the lack of unequivocal clinical benefits of HIV-1 Immunogen despite almost 30 years of extensive testing, it does not appear, in our view, that this vaccine is a clinically effective immunotherapy. However, inclusion of this vaccine in the newly proposed 'Kick/Shock and Kill' strategy for HIV eradication, or use as a prophylactic vaccine, could be considered for future trials.